Pengaruh CAR, BOPO, FDR Dan NPF Terhadap Tingkat Bagi Hasil Mudharabah Dimediasi ROA Di Bank Umum Syariah Indonesia - Ismail Nura; Nurlaila Nurlaila; Marliyah Marliyah (Politeknik Ganesha Medan, 2023)
Funding products at Islamic Banks can be in the form of demand deposits, savings and time deposits. One of the most popular fund products is mudharabah deposits. The most popular sharia banking product is mudharabah deposits. Mudharabah as a fund collector that provides the largest proportion of total DPK and is not bound by third parties because the withdrawal will be made at a certain time. Mudharabah contract as a collection of funds that provides the largest proportion of the total DPK of Islamic banks. Mudharabah is also an investment product that is not bound by a third party because the withdrawal will be made at a certain time. This study wants to test whether the Capital Adequacy Ratio (CAR), Operating expenses to operating income (BOPO), Financing to Deposit Ratio (FDR) and Non-Performing Financing (NPF) have a direct and indirect effect on mudharabah at Indonesian Sharia Commercial Banks in 2017 - 2021. The type in this research is quantitative research with the method. In this study, a documentation study was used using path analysis. Based on the results of the study, it shows that the Capital Adequacy Ratio (CAR) has a direct effect on mudharabah, Operating expenses on operating income (BOPO) has an effect on mudharabah, Financing to Deposit Ratio (FDR) has no effect on mudharabah, Non Performing Financing (NPF) has no effect on mudharabah , indirectly the Capital Adequacy Ratio (CAR) has an effect on mudharabah mediated through ROA, BOPO has an effect on mudharabah through mediated Return On Assets (ROA), Financing to Deposit Ratio (FDR) has no effect on mudharabah mediated through Return On Assets (ROA) , Non Performing Financing (NPF) has no effect on mudharabah mediated through Return On Assets (ROA).